Analisis Interpretasi Filsafat Stoisisme pada Buku Filosofi Teras Karya Henry Manampiring dan Relevansinya dengan Nilai-Nilai Ekstrinsik yang Terkandung di dalam Cerita Pendek - Desra Nita Tampubolon (International Forum of Researchers and Lecturers, 2023)
The study was set to examine an interpretation of the philosophy of the course and to elevate it with a short story extrapolated value found in the mega best seller on the self-improvement volume volume entitled